ANALYSIS OF THE EFFECT OF COMPETENCE AND KNOWLEDGE SHARING ON ASN PERFORMANCE IN REGIONAL GOVERNMENT OFFICES WITH MOTIVATION AS A MEDIATION VARIABLE - Risti Nabilla; Rini Rahmawati (Adisam Publisher, 2026)
Excellent employee performance is a requirement in the assessment of ASN work results. Competence and knowledge are one aspect of the assessment. Thus, it is important for agencies to continue to develop the abilities and knowledge of their employees. With strong motivation in performing superiorly, individuals are required to continue to develop themselves and share their knowledge. The research conducted is a quantitative descriptive study. All ASN working in the Tanah Laut Regency Regional Secretariat Office, totaling 108 people, were the samples in this study. This study uses sampling with census sampling techniques and uses the PLS- SEM analysis tool. From the results obtained, this study concludes that (1) competence has a significant positive effect on motivation in Civil Servants in the Tanah Laut Regency Regional Secretariat Office; (2) knowledge sharing has a significant positive effect on motivation in Civil Servants in the Tanah Laut Regency Regional Secretariat Office; (3) competence has a significant positive effect on the performance of Civil Servants at the Regional Secretariat Office of Tanah Laut Regency; (4) knowledge sharing does not have a significant positive effect on the performance of Civil Servants at the Regional Secretariat Office of Tanah Laut Regency; (5) motivation has a significant positive effect on the performance of Civil Servants at the Regional Secretariat Office of Tanah Laut Regency; (6) motivation can mediate competence on the performance of Civil Servants at the Regional Secretariat Office of Tanah Laut Regency; (7) motivation can mediate knowledge sharing on the performance of Civil Servants at the Regional Secretariat Office of Tanah Laut Regency.